GAYA HIDUP KONSUMTIF SEBAGAI DAMPAK ADANYA ONLINE SHOP DI KALANGAN MAHASISWA SOSIOLOGI ANGKATAN 2021 - Della Angelia; Edowardo Reyhan Rohmaddani; Fiki Fauzuna; Putri Anggraini; Titis Titis; Alan Sigit Fibrianto (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
Hadir nya aplikasi online shop adalah salah satu dampak dari globalisasi. Aplikasi online shop ini memudahkan banyak orang untuk berbelanja, terutama para remaja. Tak terkecuali mahasiswa Sosiologi angkatan 2021 Universitas Negeri Malang. Maka dari itu kami mengambil judul penelitian Gaya Hidup Konsumtif sebagai Dampak Hadirnya Online Shop di The presence of an online shop application is one of the impacts of globalization. This online shop application makes it easy for many people to shop, especially teenagers. No exception for Sociology students batch 2021, State University of Malang. The purpose of this study was to find out changes in student lifestyles as a result of the online shop among students majoring in Sociology batch 2021, State University of Malang. This study uses descriptive qualitative methods with open interview data collection techniques and literature study. After interviewing several students, it can be concluded that online shopping is very popular because it is easy and has many choices. Besides that, online shopping can also save time. However, this shopping habit has a negative impact among students, namely a consumptive lifestyle that is difficult to avoid. The emergence of a consumptive lifestyle as a result of the existence of an online shop is in line with Jean Baudrillard's theory of consumption society, where current consumption is not based on need but based on desire.